A zirconium methacrylate oxocluster as precursor for the low-temperature synthesis of porous zirconium(IV) dicarboxylates - Guillerm, Vincent; Gross, Silvia; Serre, Christian; Devic, Thomas; Bauer, Matthias; Férey, Gérard (Chemical communications (Cambridge, England), 2010)
The exchange of the monocarboxylate ligand of the zirconium methacrylate oxocluster Zr(6)O(4)(OH)(4)(OMc)(12) (OMc = CH(2)=CH(CH(3))COO) with dicarboxylic acids (trans,trans muconic acid and terephthalic acid) leads to porous zirconium dicarboxylates exhibiting the UiO-66 architecture; the mild reaction conditions allow the control of their particle size.